Young people's strategies for coping with parallel imaginings of the future. (November 2016) - Cook, Julia
Sociological work has often characterized the contemporary future horizon as a space crowded with risks and contingencies. This view has prompted a number of claims that young adults conceptualize the future predominantly in terms of the choices and plans that they make to mitigate against such concerns. As an extension of this logic, a number of studies have suggested that young adults conceptualize the long-term future extending beyond their own lives separately from their more immediate horizon of planning (Leahy et al., 2010;Toffler, 1974 ). This paper discusses how young adults relate to the long-term and more immediate future concurrently, and in doing so considers the points at which the strategies that they use to cope with contingency in their own lives may intersect with the ways that they approach their fears, hopes and imaginings of the long-term future. The data for this paper are drawn from an interview project in which young adults (aged 18–34) were asked to discuss their own futures, and a general idea of the future. The findings are used to form the beginnings of a typology of the approaches that young adults may adopt when engaging with the future, which is then drawn upon to propose that the ways in which they engage with the long-term future are often related to the strategies that they employ when facing their own futures.